Crystal structure of meso‐substituted pyrazolyl porphyrin complexes and their highly active catalyst for oxidation of alkylbenzenes. (18th December 2017) - Yao, Yahong; Du, Yanxia; Li, Jun; Wang, Chen; Zhang, Zengqi; Zhao, Xin
Abstract : During the past few years, a great deal of effort has been devoted to the anchoring of catalytic oxidation. In this work, three new catalysts CuPp, MnPp and ZnPp by solvothermal methods with 5, 10, 15, 20‐tetrakis(4‐N‐pyrazolyl)‐phenyl porphyrin (H2 Pp) and the corresponding metal salts have been synthesized and structurally characterized. The single crystal structures determined by X‐ray diffraction show the bond distances of M‐N in porphyrin cores determined the conformation of porphyrin rings. We explored the catalytic activity of CoPp, CuPp, MnPp and ZnPp for oxidation of alkylbenzenes. The experimental results display these products exhibit high catalytic activities and selectivities for oxidation of ethylbenzene to acetophenone, and can be reused by filtration without appreciable decrease in catalytic activity and selectivity. Abstract : Four kinds of catalysts CoPp, CuPp, MnPp and ZnPp derived from pyrazole‐functionalized poryphyrin exhibited high catalytic activities and selectivities for oxidation of alkylbenzenes.